2019
DOI: 10.1016/j.omtn.2019.08.012
|View full text |Cite
|
Sign up to set email alerts
|

hsa_circ_0092306 Targeting miR-197-3p Promotes Gastric Cancer Development by Regulating PRKCB in MKN-45 Cells

Abstract: Gastric cancer (GC) is one of the most common cancers worldwide and is thus a global cancer burden. Here, we focused on a novel circular RNA hsa_circ_0092306 and explored the potential molecular mechanism to provide a new target for and novel insights into GC treatment. The GEO microarray was mined and analyzed with R software. Sanger sequencing and RNase R assay were applied to verify the identification of hsa_circ_0092306. Quantitative real-time PCR and western blot were performed to measure the mRNA and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 34 publications
(37 reference statements)
2
24
0
Order By: Relevance
“…According to previous studies, miR-197-3p plays an oncogenic role in breast cancer, bladder cancer and thyroid cancer (19,20,42,43). However, the anti-oncogenic role of miR-197-3p has been found in prostate cancer and gastric cancer (44,45). In the present study, the findings were consisted with those of previous studies, which suggests the promoting effects of miR-197-3p on the progression of OS.…”
Section: Discussionsupporting
confidence: 79%
“…According to previous studies, miR-197-3p plays an oncogenic role in breast cancer, bladder cancer and thyroid cancer (19,20,42,43). However, the anti-oncogenic role of miR-197-3p has been found in prostate cancer and gastric cancer (44,45). In the present study, the findings were consisted with those of previous studies, which suggests the promoting effects of miR-197-3p on the progression of OS.…”
Section: Discussionsupporting
confidence: 79%
“…For instance, Yang et al suggested that circ-HuR was weakly expressed in GC and its overexpression repressed GC cell growth and metastasis in vivo and in vitro [23]. Du et al reported that circ_0092306 was increased in GC and accelerated GC progression via inhibiting GC cell apoptosis and inducing viability and mobility [24]. The data of Yang et al and Du et al suggested that circRNAs play different roles in GC development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we discovered that high expression of circFAM114A2 may heighten the apoptosis rate of BCa cells. Many studies have shown that circRNAs can in uence the apoptosis level of gastric cancer, urothelial carcinoma and non-small cell lung cancer cells (41)(42)(43). Hence, our results suggest that improved sensitivity induced by circFAM114A2 may also relate to a high apoptosis rate.…”
Section: Discussionsupporting
confidence: 52%